The teachers’ professional self-assessment in the mirror of a qualitative content analysis (Training and Practice : Journal of Educational Sciences, 2018)
The concepts of self-reflexion and self-assessment have become the key elements of the teachers’ professional development in Hungary with the introduction of the Teachers’ Career Model. The concepts are new for most of the Hungarian teachers. Therefore, our research is addressed to clarify what the teachers mean by these two notions and whether they apply them in their everyday professional life. In the frame of the qualitative research paradigm, we made half-structured interviews with six teachers with a wide scope of professional background. We conducted qualitative content analysis applying the Step by step model by Philipp Mayring. The results of our investigation show that self-assessment is constantly present in the teachers’ professional life. Furthermore, we could identify some specific categories to construct the concept of self-assessment. The results of our research will be used to work out the measuring tool of a wider scale quantitative research within a nested research pattern.